LEGAL PROTECTION FOR CONSUMERS IN TRANSACTIONS FOR E-COMMERCE - Bing Yusuf (UNTAG Law Review, 2019)
The development of information and electronic technology every time becomes faster, supported by the great curiosity of humans to make information technology and electronics as daily consumption. Technology penetrated into the business world pampering the community with ease of accessibility through ecommerce systems. People enjoy buying and selling facilities through e-commerce, but most people forget that every thing has a positive and negative side. The majority of people enjoy the convenience and convenience of e-commerce to access and obtain the desired items, but not a few community members have become victims of e-commerce transactions. The government acting as a regulator has issued a lot of laws and regulations, but until now all forms of injustice, fraud, and even crime through ecommerce buying and selling have not been completely blocked. Institutions established specifically to defend disadvantaged consumers also do not yet have adequate specifications to protect disadvantaged consumers through e-commerce buying and selling. The capabilities and facilities possessed by law enforcement officers are still limited, there are still many perpetrators of injustice, fraud and crime in buying and selling e-commerce that are still moving and operating freely. Based on the reality of e-commerce buying and selling formulated a problem regarding how legal protection is actually for consumers in buying and selling e-commerce? What obstacles are faced by consumers to get legal protection in buying and selling e-commerce? How is the legal effort made by consumers who are disadvantaged in buying and selling ecommerce? Using positive law analyzed with reality that occurs in the community it can be concluded that e-commerce buying and selling is arguably a new thing so that it demands for the whole legal system and legal subjects to adapt to technological developments and the progress of civilization